Introduced American eels Anguilla rostrata in European waters: life‐history traits in a non‐native environment. Issue 6 (30th April 2014) - Marohn, L.; Prigge, E.; Hanel, R.
<x xml:space="preserve">Abstract</x> This study investigated growth, condition and development of American eels Anguilla rostrata that were introduced into a European river to estimate their competitive potential in a non‐native habitat. Results demonstrate that A. rostrata develops normally in European waters and successfully competes with the native European eel Anguilla anguilla. In addition, A. rostrata appears to be more susceptible to the Asian swimbladder nematode Anguillicola crassus than A. anguilla and could support the further propagation of this parasite. Detected differences in fat content and gonad mass between Anguilla species are assumed to reflect species‐specific adaptations to spawning migration distances. This study indicates that A. rostrata is a potential competitor for the native fauna in European fresh waters and suggests strict import regulations to prevent additional pressure on A. anguilla and a potential further deterioration of its stock situation.